SHARIA-COMPLIANT CREDIT CARD EXPOSURE AND UTILISATION IN THE GROWING DIGITAL ECONOMY - Arsyianti, Laily Dwi; Adelia, Adelia (Journal of Islamic Monetary Economics and Finance, 2019)
Many cashless payment tools have been introduced into the Indonesia market inthe form of electronic money cards. The Sharia-compliant credit card is a traditionalelectronic payment tool, but is provided by only two Islamic finance institutions amongthe many in Indonesia. The increase in Sharia-compliant credit card transactions overtime may mean banks are exposed to non-performing risk. Customer behaviour variesin the use of such cards, and this may cause unpredicted results with regard to cardperformance. Therefore, the purposes of this study are: 1) to identify the behaviourof Sharia-compliant credit card users and 2) to analyse the factors which influencethis behaviour. The primary data were gathered by distributing questionnaires with atotal sample of 170 respondents and were analysed by employing structural equationmodeling. The research shows that gender, age, and education influence perceivedbehaviour control, and that expenditure influences subjective norms. Customers’attitudes, subjective norms and perceived behaviour control are proven to influencetheir intentions, while customers’ intentions, perceived behaviour control and incomeinfluence their behaviour when using Sharia-compliant credit cards. For furthersustainable inclusive growth, issuers should pay attention to education for specificaudiences.